2021
DOI: 10.1186/s12893-021-01084-8
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review on the rational use of amniotic membrane allografts in diabetic foot ulcer treatment

Abstract: Background Diabetic foot ulcer is a complication with multiple aetiological factors which has a significant impact to patients’ lives and costs to the healthcare system. The potential of human amniotic membrane to act as an allograft has been studied in relation to this condition. Aim of this study is to evaluate the current scientific evidence on its effectiveness in healing diabetic foot ulcers. Methods Pubmed, Cochrane library, and Google schola… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 17 publications
1
20
0
1
Order By: Relevance
“…Our results can be explained by the fact that thawed living amnio-chorionic membrane provides delivery to the wound of numerous regulatory proteins, which include chemokines and cytokines, as well as angiogenic proteins [26,74]. The influence of growth factors, in particular EGF, KGF, HGF, bFGF, TGF β and extracellular matrix, produced by placental tissue cells has been shown to be crucial in wound healing and to achieve complete closure [9,80,81,82].…”
Section: Resultsmentioning
confidence: 85%
See 1 more Smart Citation
“…Our results can be explained by the fact that thawed living amnio-chorionic membrane provides delivery to the wound of numerous regulatory proteins, which include chemokines and cytokines, as well as angiogenic proteins [26,74]. The influence of growth factors, in particular EGF, KGF, HGF, bFGF, TGF β and extracellular matrix, produced by placental tissue cells has been shown to be crucial in wound healing and to achieve complete closure [9,80,81,82].…”
Section: Resultsmentioning
confidence: 85%
“…Chronic wounds that did not heal for a long time with standard treatment regimens were successfully regenerated under the influence of AM allografts. In addition, the frequency of recurrences after their healing decreased [81].…”
Section: Resultsmentioning
confidence: 98%
“…Other available treatments that utilize growth factors and chemokines are Platelet-rich plasma (PRP) and amniotic membrane allografts (reviewed in [6]). PRP contains the plasma fraction with high concentrations of platelets and thereby increases the amount of growth factors such as TGF-β, PDGF, and epidermal growth factor (EGF) in the wound following release from platelets [43,44]. Amniotic membranes allografts have in multiple studies been shown to have a clinical effect on non-healing wounds, and there are some commercially available options (EpiFix, MiMedx Group, and the Grafix, Osiris Therapeutics) [45].…”
Section: Discussionmentioning
confidence: 99%
“…However, further investigations documenting the efficacy of allogeneic PRP in treatment of non-healing wounds especially are needed [11]. Furthermore, amniotic membrane allografts and other human-derived membranes have in multiple studies shown clinical effect in non-healing wounds, and there are some commercially available options, but only in a limited number of countries [12]. Neither membranes nor derivatives thereof of human origin, or autologous/allogeneic PRP represents completely defined products due to sourcing and handling during their preparation.…”
Section: Current Landscape Of Drug Developmentmentioning
confidence: 99%